(untitled) (Research, Society and Development, 2023)
Histological staining is an essential technique for the cellular and tissue study of organs, which makes it possible to identify structural components with the help of dyes. Some staining techniques have gained dominance in laboratory routine, although many synthetic dyes used contain high toxicity, which leads to the growing search for alternative natural histological dyes. In this sense, the objective of this work is to evaluate the coloring potential of pigments obtained from nine plant species derived from and remaining from the Atlantic Forest in sections of animal and plant tissue. The results showed that six extracts promoted coloring of tissue components of the intestine, heart, brain and skin of rats. Collagen fibers were evidenced by Croton floribundus, Croton urucurana, Ocotea odorífera, Xylopia brasiliensis, and mucopolysaccharides by Croton floribundus and Croton urucurana. Vascular structures and cell walls in plant tissue sections were highlighted in Solidago microglossa staining. And finally, the possible potential of some species derived from the Atlantic Forest was proven and may contain important staining value and contribute to the development of alternative means of histological staining.